Abandonment of treatment and smoking cessation: analysis of data from a control program - Bruna Vanti da Rocha; Danielle Soares Rocha Vieira; Ione Jayce Ceola Schneider (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the profile of smokers undergoing treatment and the factors associated with smoking cessation and smoking cessation in a municipal programo of treatment. Method: cross-sectional study carried out in Araranguá, state of Santa Catarina, with 109 people from the Tobacco Control Program, between March and December of the year 2018. Sociodemographic and health information, including depressive symptoms, impulsivity and coping skills, were collected. Descriptive and inferential analyzes were carried out. Results: 40.4% of the participants abandoned the treatment, group that obtained the highest mean for impulsivity. The main reasons reported for abandoning treatment were: "being well without smoking", work-related situations and withdrawal symptoms. It was observed that 7.64% quit smoking and 93.8% had mild dependence on nicotine. Conclusion: although abandonment is high, some remained in cessation. Those aged 49 years or less were significantly more abandoned and nicotine addiction is a significant impediment to cessation.